Completeness of information in electronic compared with paper-based patients’ records in a maternity setting in Dakar, Senegal - Ndiaye, Mame D.; Gueye, Mamour; Ndour, Simon B.; Niang, Ndama; Fall, Ndeye G.; Fall, Khalifa; Diakhate, Abdoulaye; Wade, Mouhamadou; Diouf, Aliou; Diallo, Moussa; Mbaye, Magatte (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Evaluate the consistency of information in paper-based records when registered in parallel with an electronic medical record. Methods: The study was performed at PMSHC in Dakar Senegal. From the end of year 2016, patients’ files were recorded on both paper-based and electronically. Additionally, previous records were electronically registered. To investigate the completeness of records before and after the electronic recording system has been implemented, information about some maternal and fetal/neonatal characteristics were assessed. When the variable was recorded, the system returned 1, unrecorded variables were coded as 0. We then calculated, for each variable, the unrecorded rate before 2017 and after that date. The study period extended from 2011 to June 2019, a nearly ten-year period. Data were extracted from E-perinatal to MS excel 2019 then SPSS 25 software. Frequencies of unrecorded variables were compared with chi-squared test at a level of significance of 5%. Results: A total of 48,270 unique patients’ records were identified during the eight-year period. Among the study population, data for patients’ age, address and parity were available most of the time before and after 2017 (0.5% missing data versus 0.3% for age and 2.6% versus 1.3% for home address and from 0.3% to 0.0% for parity). However, phone number, maternal weight, maternal height, last menstrual period and blood group were found to be missing up to 96% before 2017. From 2017, these rates experienced a sudden decrease at a significant level: from 82.4% to 27.8% for phone number, from 96% to 56.3% for maternal weight and from 60.1% to 21.3% for blood group. Regarding newborns’ data, it was found that fetal height, head circumference and chest circumference were missing up to just under 25% before 2017. After that date, their completeness improved and flattened under 5%. Conclusions: Structured and computerized files reduce missing data. There is an urgent need the Ministry of health provides hospitals and health care providers with guidelines that describes the standardized information that should be gathered and shared in health and care records.